IMPLEMENTASI PEMBIASAAN SHALAT DHUHA DALAM PEMBENTUKAN KARAKTER DISIPLIN SISWA DI SEKOLAH MADRASAH IBTIDAIYAH BAIT QU’ANY BSD - Widaryanti, Emi; Maulidin , Syarif; Andrianto, Dedi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Character education has become one of the primary objectives of Islamic educational institutions in developing students who possess not only academic competence but also positive moral values. One of the strategies implemented to strengthen students' character is the habituation of religious practices, including the regular performance of Dhuha prayer. This study aims to analyze the implementation of Dhuha prayer habituation in fostering students' disciplinary character at Madrasah Ibtidaiyah (MI) Bait Qur'any BSD, to examine its contribution to character formation, and to identify the supporting and inhibiting factors affecting its implementation. This research employed a qualitative descriptive approach. Data were collected through observations, in-depth interviews, and documentation involving the principal, Islamic Religious Education teachers, classroom teachers, and students. The collected data were analyzed using the interactive model of data reduction, data display, and conclusion drawing. The findings reveal that the habituation of Dhuha prayer has been systematically integrated into the school's daily religious culture and consistently implemented before classroom learning activities. The program contributes positively to the development of students' disciplinary character, particularly in terms of punctuality, compliance with school regulations, and responsibility in carrying out academic and religious duties. The success of the program is supported by the commitment of school leaders, teachers' exemplary behavior, adequate facilities, and parental involvement, while differences in students' awareness and limited supervision outside school remain the main challenges. Therefore, the habituation of Dhuha prayer can be considered an effective strategy for strengthening disciplinary character among elementary-level students in Islamic schools.